2012
DOI: 10.1002/ibd.22947
|View full text |Cite
|
Sign up to set email alerts
|

Role of LFA-1 in the activation and trafficking of T cells: Implications in the induction of chronic colitis

Abstract: The objectives of this study were to assess the role of LFA-1 in enteric antigen (EAg)-induced activation of T-cells in vitro and in vivo and to define the importance of this integrin in promoting trafficking of T-cells to the MLNs and colon. We found that EAg-pulsed dendritic cells (DCs) induced proliferation of LFA-1-deficient (CD11a−/−) CD4+ T-cells that was very similar to that induced using WT T-cells suggesting that LFA-1 is not required for activation/proliferation of T-cells in vitro. Co-culture of WT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…Here, Wang and coworkers demonstrated that the TGF-ß secretion of Treg required the expression of CD18 [ 206 ] and that LFA-1 is essential for an effective inhibition of T cell proliferation [ 207 ]. In accordance with these findings, the importance of LFA-1, expressed on T cells, for the induction of tolerance and the suppression of inflammation has been documented in various autoimmune diseases, such as experimental autoimmune encephalitis (EAE) [ 208 , 209 ], systemic sclerosis [ 210 , 211 ], rheumatoid arthritis, psoriasis [ 193 , 212 ], or systemic lupus erythematosus [ 213 , 214 ]. Notably, in most of these diseases, expression levels of CD11a on T cells inversely correlated with the severity of the disease [ 213 , 215 , 216 ].…”
Section: The Role Of β2 Integrins For the Immune Regulatory Tumor mentioning
confidence: 79%
“…Here, Wang and coworkers demonstrated that the TGF-ß secretion of Treg required the expression of CD18 [ 206 ] and that LFA-1 is essential for an effective inhibition of T cell proliferation [ 207 ]. In accordance with these findings, the importance of LFA-1, expressed on T cells, for the induction of tolerance and the suppression of inflammation has been documented in various autoimmune diseases, such as experimental autoimmune encephalitis (EAE) [ 208 , 209 ], systemic sclerosis [ 210 , 211 ], rheumatoid arthritis, psoriasis [ 193 , 212 ], or systemic lupus erythematosus [ 213 , 214 ]. Notably, in most of these diseases, expression levels of CD11a on T cells inversely correlated with the severity of the disease [ 213 , 215 , 216 ].…”
Section: The Role Of β2 Integrins For the Immune Regulatory Tumor mentioning
confidence: 79%
“…S6B), indicating that Mef2d inhibits CD4 T cells from establishing antigen-specific B:T synapse. We assessed expression of Vα2, the TCR α chain of the OTII TCRtg CD4 T cells ( 51 ), and CD18 (β 2 integrin subunit of LFA-1), the lack of which compromises LFA-1 function in CD4 T cells ( 52 ). Expression of both Vα2 and CD18 was comparable between Mef2d-RV and control OTII CD4 T cells (fig.…”
Section: Resultsmentioning
confidence: 99%
“…CD11a −/− mice presented with a reduced frequency of immuno-suppressive Treg fraction in the CNS, which resulted in more severe EAE after immunization [258]. Likewise, CD18 expression was found to be necessary for Treg induction [259,260]. Thus, on one hand transfer of encephalogeneic WT T cells to CD11a −/− mice-lacking Treg-caused a fatal course of the EAE [261].…”
Section: Lfa-1mentioning
confidence: 99%